The Disconnect between Financial Compliance and Pedagogical Utility in School Management: A Phenomenological Study on “Sleeping Assets” and Bureaucratic Rituals - Novie Noldy Johanes Rompis; Henny Nikolin Tambingon; Rolles N. Palilingan; Ruth Umbase (JR Education, 2026)
In the landscape of decentralized school-based management, principals hold a complex dual autonomy: as accountable fiscal managers and as visionary instructional leaders. However, the pressure of bureaucratic isomorphism often creates an extreme disparity in focus. This phenomenological study investigates how principals in Public Junior High Schools (SMP) in Tomohon City, Indonesia, navigate the existential tension between the demands for state financial reporting compliance and the effectiveness of asset utilization for learning. Through in-depth interviews, document analysis, and physical observation of schools, this study uncovers a chronic phenomenon of “Loose Coupling.” The findings indicate that: (1) An Asymmetry of Accountability occurs, where leadership energy is exhausted pursuing an administrative “clean audit” status, while the evaluation of pedagogical impact is neglected; (2) The emergence of the “Sleeping Assets” phenomenon, where teaching aids and learning technologies undergo an ontological death—purchased as symbols of modernity but unused in classroom practice; and (3) External evaluation tends to be blunt and normative, failing to diagnose the gap between budget expenditure and learning quality. This study concludes that without reforming accountability mechanisms to balance fiscal and pedagogical indicators, educational decentralization will only produce symbolic compliance without substantial quality improvement.